Vittorio G. Rossi. Il silenzio di Cassiopea. Ed. Mondadori. Verona. 1965. 268 p., 13 x 20 cm. - Chiapasco, María Elena (1967)
Fil: Chiapasco, María Elena. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras